2022
DOI: 10.1109/tbc.2022.3140710
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Quality Assessment of HEVC and VVC Standards for 8K Video

Abstract: With the growing data consumption of emerging video applications and users' requirement for higher resolutions, up to 8K, a huge effort has been made in video compression technologies. Recently, versatile video coding (VVC) has been standardized by the moving picture expert group (MPEG), providing a significant improvement in compression performance over its predecessor high efficiency video coding (HEVC). In this paper, we provide a comparative subjective quality evaluation between VVC and HEVC standards for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…We down-converted the 8K videos to 2K (1,920×1,080), 4K, and 6K (5,760×3,240) spatial resolutions with the same 60 Hz temporal framerate to generate distorted videos. For all the down-and upconversion processes, the Lanczos-3 filter [14] using FFmpeg 3 was applied according to previous studies [5], [15]. Next, we load the down-converted and 8K original videos to the encoder.…”
Section: K Subjective Evaluation Experiments a Test Videosmentioning
confidence: 99%
See 4 more Smart Citations
“…We down-converted the 8K videos to 2K (1,920×1,080), 4K, and 6K (5,760×3,240) spatial resolutions with the same 60 Hz temporal framerate to generate distorted videos. For all the down-and upconversion processes, the Lanczos-3 filter [14] using FFmpeg 3 was applied according to previous studies [5], [15]. Next, we load the down-converted and 8K original videos to the encoder.…”
Section: K Subjective Evaluation Experiments a Test Videosmentioning
confidence: 99%
“…The actual bitrates and QP values are shown in Table 2. A previous study on 8K subjective evaluations revealed that VVC exhibits an average of approximately 41% of bitrate reduction over HEVC for the same visual quality [5]. Therefore, we considered that target bitrates widely cover video quality from low to high in this range.…”
Section: K Subjective Evaluation Experiments a Test Videosmentioning
confidence: 99%
See 3 more Smart Citations